Implementation of Sorting Algorithm in Marketplace to Sort Price Using Insertion Sort - Qowy, Bilal Abdul; Chalik, Amanda Muchsin; Hanafi, Faiz; Sundawijaya, Andika (Jurnal Teknik Informatika dan Elektro, 2022)
Price is the first thing that customers look at before they buy something. So, sorting is the most important feature that every single person needs when we want to shop on the online marketplace or we can call it e-commerce. In this case we would focus on the price, because price is the most important thing that customers consider before they buy something. However, customers see each other too closely but price is the most important thing. Sort Algorithm is not just about Insertion Sort , there are many of them, like bubble sort , Quicksort, mergesort, etc. but we use insertion sort based on the runtime complexities and find the fastest time to reach the final results. And our implementation in the website base, it is common to use and implement on that scope.